The Rise of Modern Angolan Parties – UNITA and a Failed Growth Model - SANTOS Maciel (Ученые записки Института Африки Российской академии наук)
During the 1960’s the extension of the capitalist mode of production fastened the disintegration of the Angolan “traditional society”. Angola’s high-rate growth was made possible because huge oil and diamond rents were taxed and reinvested locally. With these “development polices” which the colonial State expected would support the fading branches of agro-industry and stabilize the political status quo, there was a shift of the main social contradiction. It was no longer a “central” versus “tributary” cleavage but rather labour-capital one within “modern society”. Ideologically, although transitional languages expressed by “racial” or cultural phenotypes were still in use, there was now room for different political standings. The nationalist movements, which started as small dissent fractions within the “central society“ were therefore forced to change their tactics in order to encompass the support of rising classes and their social mobility aspirations. This paper focuses on UNITA, whose operational circumstances (guerrilla-based operations inside Central Angola) made it easier to fit into the moving social landscape. Some evidences of UNITA ideological stand and of its 1974-1975 electoral behaviour (a period when the guerrilla movements were facing metamorphose into political parties) show that the factor “ethnicity”, widely used as a key variable of African politics, needs reviewing, at least in this particular time in Angola.